(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article develops strategies for the development of international companies in modern conditions; the basic concepts of the development strategy of international companies in modern conditions are revealed; analyzed the activities of the association "Uztekstilprom"; practical proposals have been developed to improve the development strategy of the association "Uztekstilprom"